Anionic high-entropy doping engineering for electromagnetic wave absorption - Jiaqi Tao; Yi Yan; Jintang Zhou; Jin Wang; Ping Chen; Ruiyang Tan; Linling Xu; Hongbao Zhu; Wenhui Zhu; Hexia Huang; Xuewei Tao; Zhengjun Yao (Nature Communications)
Abstract High-entropy doping (HED) engineering surpasses conventional methods for optimizing atomic configurations and electronic structures, opening new paths for developing advanced electromagnetic wave absorbing (EWA) materials. However, the application of anionic HED engineering to tailor EWA mechanisms remains unexplored. Herein, we employ in situ pyrolysis combined with a three-stage solvent thermal doping procedure to systematically induce anion multibody interactions, thereby facilitating the inheritance and accumulation of beneficial EWA properties. The research shows that anions with various electronegativities precisely balance free charges and create a significant localized charge imbalance, triggering the ‘directional cocktail effect’. This effect induces an optimal dielectric loss mechanism and enhances the EWA performance. With only 7.5 wt% filling, the effective absorption bandwidth and minimum reflection loss are 7.05 GHz and −60 dB, respectively. Overall, we report an anionic HED engineering within thin a graphite framework, which may be conceptually extendable for electromagnetic modulation of other two-dimensional van der Waals EWA materials.